A China – US bilateral investment treaty: A template for a multilateral framework for investment? - Karl P. Sauvant; Huiping Chen (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2012)
A bilateral investment treaty between China and the US would not only be of importance for the economic relations of the world's two largest economies, but could also become a template for a multilateral framework for investment. This Perspective looks at key outstanding issues in the China-US negotiations and identifies alternative compromises.
Keywords: 330